Factors affecting the quality of biomass pellet for biofuel and energy analysis of pelleting process - Adapa, Phani K.; Tabil, Lope G.; Schoenau, Greg J. (International Journal of Agricultural and Biological Engineering, 2013)
Agricultural biomass residue such as barley, canola, oat and wheat straw has the potential to be used for sustainable production of bio-fuels and offset greenhouse gas emissions. The biomass substrate must be processed and handled in an efficient manner in order to reduce industry’s operational cost as well as meet the requirement of raw material for biofuel production. Biomass has low bulk density, making it difficult and costly to store and transport in its native loose form. Therefore, in this study, an integrated approach to densification of non-treated and steam exploded barley, canola, oat and wheat straw was developed. During this process, the significance of major contributing factors (independent variables such as biomass type, treatment, pressure and grind size) on pellet density, durability and specific energy were determined. It has been found that applied pressure (60.4%) was the most significant factor affecting pellet density followed by the application of steam explosion pre-treatment (39.4%) for lab-scale single pelleting experiments. Similarly, the type of biomass (47.1%) is the most significant factor affecting durability followed by the application of pre-treatment (38.2%) and grind size (14.6%) for pellets manufactured using the pilot-scale pellet mill. Also, applied pressure (58.3%) was the most significant factor affecting specific energy required to manufacture pellets followed by the biomass (15.3%), pre-treatment (13.3%) and grind size (13.2%), which had lower but similar effect on specific energy for lab-scale single pelleting experiments. Overall energy analysis of post-harvest processing and densification of agricultural straw was performed, which showed that a significant portion of original agricultural biomass energy (89%-94%) is available for the production of biofuels. Almost, similar amount of specific energy is required to produce pellets from barley, canola, oat and wheat straw grinds. Customized pellets having steam exploded straw required more energy to manufacture resulting in availability of only 89% of total energy for biofuel production.